2016
DOI: 10.14513/actatechjaur.v9.n2.402
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Need for Applying Multimodal Speed Distribution in Road Transport Macro Emission Estimation

Abstract: Vehicles speed distribution is an important input parameter in lots of issues, such as kinematical traffic simulation model, road design, speed limit evaluation, road traffic noise prediction or vehicles emission estimation. In this paper, a new approach has been presented in which the speed is randomly generated according to different speed distributions. Later on, these distributions were used as the basis of emission estimation. These different distributions were chosen according to the contextual traffic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The development of mathematical tools focused on the modelling of the speed distribution in a traffic flow is widely reported in the scientific literature [21][22][23][24]. Many papers concern this problem since vehicles speed distribution is an important input parameter in lots of issues, such as kinematical traffic simulation model, road design, speed limit evaluation, road traffic noise prediction, traffic safety evaluation, bicycle performance evaluation, analysis of pedestrian walking, road transport emission estimation [25][26][27][28][29][30][31][32][33], [46] etc. Since 1940 majority of papers considered speed distribution as Gaussian or Normal distribution (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The development of mathematical tools focused on the modelling of the speed distribution in a traffic flow is widely reported in the scientific literature [21][22][23][24]. Many papers concern this problem since vehicles speed distribution is an important input parameter in lots of issues, such as kinematical traffic simulation model, road design, speed limit evaluation, road traffic noise prediction, traffic safety evaluation, bicycle performance evaluation, analysis of pedestrian walking, road transport emission estimation [25][26][27][28][29][30][31][32][33], [46] etc. Since 1940 majority of papers considered speed distribution as Gaussian or Normal distribution (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…multimodal. For example, in measurement of speed distribution of road traffic vehicular data is multimodal (Torok and Zefreh, 2016), where the authors found that the emission level for applying combined multimodal speed distribution function was lower as compared to unimodal speed distribution. Haze particle size in a chemically oxidising atmosphere follows multimodal distribution (Fan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, different traffic conditions have been represented by the distribution of traffic speed in that traffic condition obtained by on-field data collection. It is worth to mention that the role of speed distribution on road traffic emission [29] and noise has been investigated in the literature. For instance, the effects of speed distributions on the Harmonoise model predictions have been investigated by [30].…”
Section: Introductionmentioning
confidence: 99%